Usage of complementary medicine across Switzerland (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: This study investigated the use among the Swiss adult population and regional dissemination of various methods of complementary medicine (CM) provided by physicians or therapists in Switzerland. METHODS: Data of the Swiss Health Survey 2007 were used, which comprised a telephone interview followed by a written questionnaire (18,760 and 14,432 respondents, respectively) and included questions about people's state of health, health insurance and usage of health services. Users and non-users of CM were compared using logistic regression models. RESULTS: The most popular CM methods were homeopathy, osteopathy, acupuncture and shiatsu/foot reflexology. 30.5% of women and 15.2% of men used at least one CM method in the 12 months preceding the survey. Lake Geneva region and central Switzerland had more CM users than the other regions. Women, people between 25 and 64 years of age and people with higher levels of education were more likely to use CM. 53.5% of the adult population had a supplemental health insurance for CM treatments. 32.9% of people with such an insurance used CM during the 12 months preceding the survey, and so did 12.0% of people without additional insurance. CONCLUSIONS: Almost one fourth of the Swiss adult population had used CM within the past 12 months. User profiles were comparable to those in other countries. Despite a generally lower self-perceived health status, elderly people were less likely to use CM.